Data Analysis and Mining - Stefanos Ougiaroglou; Dionisis Margaris (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The research field of data analysis and mining has attracted the interest of both academia and industry in recent years. This reprint contains 17 papers, which cover different topics of the broad research field of data analysis and mining. Each paper presents new data mining algorithms and techniques, as well as applications of data analysis and mining in real-world domains.
Keywords: 519; chi-square test; constrained likelihood ratio test; Fisher test; gamma distribution; uniformly most powerful test; key interested frame; commodity video; clustering; deep neural network; frequent subtree; parallel algorithms; data partitioning; load balancing; trust inference; trust propagation; online social network; social network analysis